The burden of Galileo's controversy: the Jesuit revisiting of the Aristotelian cosmos in Collegio Romano (1618-1677) - Luís Miguel Carolino (Galilæana)
While studying the controversy between Galileo and the Jesuits over the comets of 1618, historians tend to focus on the works that led to the publication of Il Saggiatore in 1623. This article demonstrates that the echoes of this controversy resounded even through the Collegio Romano far beyond the publication of Galileo's masterpiece. Here the professors of philosophy and mathematics had striven for decades to maintain - against Galileo - the Aristotelian principle that the heavens were ontologically superior to the terrestrial region. Even after adhering to Tycho Brahe’ planetary model as well as to the idea of celestial fluidity, they persisted in arguing that there could be no corruption in the celestial region. Hence, by accepting Tycho’s astronomical theories the seventeenth-century professors of the Collegio Romano did actually reject the Ptolemaic astronomical framework, but not necessarily the very core of the Aristotelian cosmology. The Collegio Romano remained the champion of philosophical orthodoxy within the Jesuit educational network.